The Role of ACE Gene Rs 1799752 I/D Polymorphism and Serum ACE Activity in Recurrent Miscarriage Pathogenesis in Iraqi Women - Kareem, Hiran J.; I. A., Abdulhassan (Journal of Neonatal Surgery, 2025)
Background Recurrent miscarriage is a major health public health problem that affects one to three percentage of women of childbearing age and is diagnosed as a spontaneous miscarriage if happened more than two times and occur often to the completion of 20 weeks amenorrhea. The variation in Angiotensin-Converting Enzyme (ACE) may be have an important role in the recurrent miscarriages (RM) in Iraqi women. Objective The present study aimed to investigate the role of ACE gene polymorphism and its serum level in the pathogenesis of recurrent miscarriage in Iraqi women. Materials and methods: Blood samples were collected from fifty patients with RM of unknown cause and fifty apparently healthy women (control). DNA was extracted for genotyping and serum samples were obtained to determine the concentration of ACE activity. ACE gene polymorphisms were determined by using Polymerase Chine Reaction –High Resolution Melting (PCR-HRM), while, serum level of ACE were determined by using Enzyme-Linked Immunosorbent Assay (ELISA). Results The research data indicated that genotype II was accompanied by a lower risk of recurrent miscarriage, while there is no relation was obtained of allele frequency among the recurrent miscarriage cases. Moreover, it’s showed that there is a significant differences were noted between RM patients and controls as related with serum ACE level. High ACE activity was noted in the RM patients carrying D allele in compared to healthy individuals. In all trimesters of the RM incidence was higher in the ID genotype carriers and 70% of RM patients were in the first trimesters. Conclusion These results concluded that the ACE gene polymorphism at rs179952 have a role in the RM pathogenesis and the genotype II may serve as a protective factor against RM, it’s also showed that there is a low serum ACE levels which might be a new marker for recurrent miscarriage risk in Iraqi women. The results also showed that there is a strong association between the rs1799752 genetic polymorphism in the ACE gene and the increased risk of miscarriage, especially in pregnant women carrying the ID genotype.